Mental health problems in male young offenders in custodial versus community based-programs: implications for juvenile justice interventions - Rijo, Daniel (2016)
Young offenders are known to be a population with high prevalence of mental health disorders. In most cases, these disorders are neither identified nor treated properly, with the majority of them being chronic and difficult to treat. In many countries, the prevalence rates of psychopathology in male young offenders are still unknown and no psychotherapeutic interventions are delivered. Therefore, the main goal of the present study was to assess mental health problems in Portuguese male young offenders placed in either custodial or community-based programs and discuss treatment implications within the juvenile justice interventions.